Peningkatkan Kemampuan Vocabulary Melalui Program â€œWeekly English For Kidsâ€ Bagi Anak-Anak Di Desa Pelem Kecamatan Pringkuku Kabupaten Pacitan Jawa Timur - Bakti Sutopo; Wisnu Ariyani (Jurnal Abdimasa Pengabdian Masyarakat, 2023)
Elementary school aged children in Pelem Village hamlet have trouble learning English. Meanwhile, children have high motivation to learn English but have not been well facilitated in the environment. The purpose of this service is to improve children’s ability to speak English properly and precisely; increase motivation to learn English; and improve academic achievement in learning English at school. The approach used is community service. Lectures, TPR (total physical response), questions and answers, ice breaking, and exercise are some of the techniques employed in this community service. Based on the results of the Weekly English for Kids program, which show that: (1) the children’s self-confidence has grown; and (2) the children’s ability to learn English seems to have increased, it is proven that the children have succeeded in working on worksheets with maximum results. In addition, the village government hopes that this community service will continue to improve children’s English skills.